Comparison of droperidol and ondansetron prophylactic effect on subarachnoid morphine-induced pruritus - Brião, Fabio Ferreira da Cunha; Horta, Marcio Leal; Horta, Bernardo Lessa; de Barros, Guilherme Antônio Moreira; Behrensdorf, Ana Paula; Severo, Ingrid; Nunes, Mariana Antunes; Boabaid, Roberta; Real, André (Elsevier, 2015)
BACKGROUND AND OBJECTIVES: The prophylactic effect of ondansetron on subarachnoid morphine-induced pruritus is controversial, while evidence suggests that droperidol prevents pruritus. The aim of this study is to compare the effects of droperidol and ondansetron on subarachnoid morphine-induced pruritus. METHODS: 180 ASA I or II patients scheduled to undergo cesarean sections under subarachnoid anesthesia combined with morphine 0.2mg were randomized to receive, after the child's birth, metoclopramide 10mg (Group I - control), droperidol 2.5mg (Group II) or ondansetron 8mg (Group III). Postoperatively, the patients were assessed for pruritus (absent, mild, moderate or severe) or other side effects by blinded investigators. Patients were also blinded to their group allocation. The tendency to present more severe forms of pruritus was compared between groups. NNT was also determined. RESULTS: Patients assigned to receive droperidol [Proportional odds ratio: 0.45 (95% confidence interval 0.23-0.88)] reported less pruritus than those who received metoclopramide. Ondansetron effect was similar to metoclopramide [Proportional odds ratio: 0.95 (95% confidence interval 0.49-1.83)]. The NNT for droperidol and ondansetron was 4.0 and 14.7, respectively. CONCLUSIONS: Ondansetron does not inhibit subarachnoid morphine-induced pruritus.
Keywords: Droperidol; Injeção subaracnoidea; Morfina; Morphine; Ondansetron; Prurido; Pruritus; Subarachnoid injection